Repositórios digitais institucionais: um viés pela lei de acesso à informação - Franco, Izabel da Mota (Universidade Federal de São Carlos, 2015)
Universities, as spaces for the production and transfer of scientific knowledge, concentrate the work of professors and researchers, generating several studies in various areas, that need to be disseminated and used to ensure the progress of science. Open Access Institutional Repositories (IRs) were created to meet this need of promoting the greater propagation of knowledge, until then hindered by the costs of access to scientific journals, especially the ones originating in Europe and the USA. In Brazil, the concern with open access is more recent; it dates from 2005, but from 2011, it was boosted with the establishment of the Information Access Act (Law No. 12.527, from 11/18/2011). This aims to extend, enforce transparency and speed up access to information to the general public, making the institutions more visible with social and economic relevance, which thus demonstrates the public value of their activities. Given this scenario, many institutions in Brazil are striving to systematically provide access to all kinds of information that they generate (the organization‟s products of an artistic, technological, academic, scientific and cultural character). This includes so-called grey literature, which is made up of technical reports, research, government publications, single translations, preprints, theses, dissertations and literature originated from scientific meetings, such as congressesannals. Under these circumstances, the scientific and functional communities of institutions can rely on the RI as a tool to retrieve, disseminate and preserve institutional memory and access to other universities and the Brazilian society. In this context, the central theme of the present research is open access, and its object of study is the concept and policies related to Institutional Repositories (IRs). The research is centered on the question of the possible need to expand the concept of Institutional Repository, going beyond being exclusively for the storage and dissemination of scientific communications. The objective of this research is to find and point out potential subsidies for the development of an IR policy that covers this wider concept. In order to do so, we will use bibliographical research, adopting systematic data collection, according to a list of terms as key points. We also conducted semi-structured interviews with stakeholders in the process of dissemination of information generated at the Federal University of São Carlos (UFSCar). Data analysis was performed qualitatively; the analytical categories were identified in the survey at the stage of bibliographical research and content analysis was used to analyze the interviews. The results of this study systematize concepts and arguments that can underpin the formulation of an IR policy to cover both the need for greater disclosure and dissemination of scientific information to the scientific community and the general public, as well as public information for the same communities.
Keywords: Comunicação na ciência; Repositórios institucionais; Acesso aberto à informação; Lei de acesso à informação; Institutional repository; Scientific communication; Open access to information; Law of access information; OUTROS